Designing a Project-Based Learning (PjBL) Model on Multiculturalism in History: Desain Model Projek Based Learning (PjBL) Tema Multikulturalisme dalam Pembelajaran Sejarah - Ulfatun Nafi’ah; Djono (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
The purpose of writing this article is to design a multiculturalism approach to teaching history; analyze opportunities and challenges regarding teaching history through a multicultural lens; and prepare a project-based learning model design with the theme of multiculturalism with material on the Cultural History of West Kalimantan. This research method is a literature review. This research uses library insights to examine 20 journal articles related to the content of the article topic. Articles are written based on secondary data sources. The data used was obtained based on research reports, books, and appropriate articles. The data collection method was carried out through a process of in-depth study and analysis of literature on multiculturalism in the history of education in Indonesia. The data analysis technique used in writing articles is qualitative analysis. This article provides insight into the multiculturalism approach to cultural history in the West Kalimantan region. The project-based learning (PjBL) learning model can be an example for teachers in designing learning models that suit the environment and conditions of students. The aim of learning with a multiculturalism approach is expected to provide good historical awareness for students to care for Indonesia's diversity and the variety of cultures that exist. In practice, students can instill an attitude of tolerant and respectful civic life, have empathy for others to create a just Indonesian nation, and uphold democratic values ​​in life.